At First Glance: Social Meanings of Dental Appearance - Ilana Eli, DMD; Yoram Bar-Tal, PhD; Ina Kostovetzki, DMD (Blackwell Synergy)
An important factor in social interaction is physical appearance. Major elements in the evaluation of physical appearance are the mouth and teeth. The purpose of this study was to evaluate the effect of tooth appearance on the development of a first impression of the other person, with regard to the sex of both the respondent and the target.